Interclonal Variation in Strength Properties of Populus deltoides from Haldwani (Uttaranchal) - Jain, V. K.; Khanduri, A. K. (Indian Forester, 2003)
The physical and mechanical properties data of six poplar clones from trial plantations grown at Haldwani (Uttaranchal) based on testing of small clear specimens are reported and discussed. The clones S7 C4 and G3 have given the highest and the lowest specific gravity of 0.418 and 0.362. respectively. This trend is also reflected in most of the strength properties. Clone G 48 has the highest growth rate and most of the nail and screw withdrawal resistance values are also higher than other clones among the different clones of Populus deltoids reported in this paper.